PERANAN ORGANISASI SISWA INTRA SEKOLAH (OSIS) DALAM MEMEBENTUK KARAKTER SISWA DI SMK NEGERI 2 SALATIGA - Indra Anggrio Toni (Universitas Kristen Satya Wacana, 2019)
One of the negative impact of globalization era is the decreasing of the character of senior high school' students. This case can be seen from many kinds of offenses of the students such as bring pornographic readings, skipping classes, smoking, and brawls. Therefore, one of the effort of the school to overcome the problems is through student council. The purpose of this research is to describe the role of the student council in forming the students' characters in Vocational High School 2 in Salatiga from (1) student council's work programs that have been arranged and done, (2)  the students character formation through student council's activities, (3) the successful implementation of student council activities in shaping the students' character. Qualitative research with a descriptive approach is used in this study  and the participants are the chairman and members of the student council, and  student council adviser. The data collection used interview, observation, and documentation. The results of the research showed:  (1) there were 4 activities or programs of student council such as class meetings, the representative meeting, the introduction of the school environment, and basic leadership training, (2) Four activities or programs formed the students' character such as discipline, confidence, responsibility, mutual respect, democracy, caring, critical, and leadership, (3) the programs are done successfully to change the students' character who were less disciplined to be more disciplined, responsible to do homework, caring to friends, critical and confident in giving opinions in front of the class or public,  cooperated well and respected to teachers.